2021
DOI: 10.1128/jcm.01885-20
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Rifampin Resistance and rpoB Mutations in Mycobacterium tuberculosis: an Analysis of Whole-Genome Sequencing and Drug Susceptibility Test Data in New York

Abstract: Rapid and reliable detection of rifampin (RIF) resistance is critical for the diagnosis and treatment of drug-resistant and multi-drug resistant (MDR) tuberculosis. Discordant RIF phenotype/genotype susceptibility results remain a challenge due to the presence of rpoB mutations which do not confer high levels of RIF resistance as have been exhibited in strains with mutations such as Ser450Leu. These strains, termed low-level RIF resistant, exhibit elevated RIF minimum inhibitory concentrations (MICs) compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
55
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 71 publications
6
55
0
2
Order By: Relevance
“…Importantly, some RRDR mutations might be excluded from the expert rule, should conclusive evidence emerge that these do not confer elevated MICs and/or are not clinically significant. The MIC data from Shea et al are in line with an earlier report from Haiti by Ocheretina et al that suggested that rpoB T427A may be one of these exceptions (6,35). However, given that this mutation appears to have evolved independently in lineages 3 and 4, which is typically a signal of selection, additional MIC testing is needed using a method for which a welldefined ECV exists and the quality control range of the laboratory strain H37Rv is not truncated to ensure high-quality testing (17).…”
Section: Genotypic Ast For Rifsupporting
confidence: 84%
See 3 more Smart Citations
“…Importantly, some RRDR mutations might be excluded from the expert rule, should conclusive evidence emerge that these do not confer elevated MICs and/or are not clinically significant. The MIC data from Shea et al are in line with an earlier report from Haiti by Ocheretina et al that suggested that rpoB T427A may be one of these exceptions (6,35). However, given that this mutation appears to have evolved independently in lineages 3 and 4, which is typically a signal of selection, additional MIC testing is needed using a method for which a welldefined ECV exists and the quality control range of the laboratory strain H37Rv is not truncated to ensure high-quality testing (17).…”
Section: Genotypic Ast For Rifsupporting
confidence: 84%
“…In this issue of the Journal of Clinical Microbiology, Shea et al add to this picture by providing evidence that the CLSI-endorsed RIF CC for the Sensititre MYCOTB broth microdilution plate by Thermo Fisher, which is not FDA approved but is CE-IVD marked in the European Union, is likely set too high (6,17). Specifically, their findings are in line with an earlier study by Torrea et al and indicate that the CC needs to be lowered to the tentative ECV of 0.5mg/ml, following a more detailed review of additional data sets (25).…”
Section: Phenotypic Ast For Rifmentioning
confidence: 99%
See 2 more Smart Citations
“…Universal clinical whole-genome sequencing could overcome the limitations of critical concentration phenotyping and partial gene sequencing and provide a more complete understanding of the prevalence and type of rpoB mutations and their association with RIF R . 27 Second, we focused only on MTB isolates of RIF R using LJ medium and the DST proportional method ; therefore, we were unable to associate treatment outcomes with various mutation types. Finally, all isolates were isolated from culture-positive sputum specimens from patients with suspected TB, and we did not include patients without isolates available for drug resistance profiles and rpoB mutations in our analyses.…”
Section: Discussionmentioning
confidence: 99%